W krzywym zwierciadle. Świat filmowców w prozie Jakuba Żulczyka = In the distorting mirror. The world of filmmakers in Jakub Żulczyk`s prose - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In Jakub Żulczyk`s prose, which abounds in allusions to feature films, television series, shows and computer games, the world of filmmakers also plays an important role. In particular, actors performing in pornographic films are frequently invoked; Żulczyk`s representations of them veer between irony or explicit contempt and the creation of "familiarity" myths.
Keywords: Żulczyk, Jakub (1983- ); proza polska; film pornograficzny; twórcy filmowi; mit; prose; pornographic films; filmmakers; myth